Synthesis of organosoluble and transparent phenolphthalein-based cardo poly(ether sulfone imide)s via aromatic nucleophilic substitution polymerization. (December 2016) - Li, Lan; Liu, Jiangtao; Chen, Guofei; Xu, Lubo; Mushtaq, Nafeesa; Sidra, Lala Rukh; Wang, Ruixin; Fang, Xingzhong
A series of cardo poly(ether sulfone imide)s (PESI-C) containing bulky phthalide groups were prepared via aromatic nucleophilic substitution reaction of phenolphthalein with 4, 4′-difluorodiphenyl sulfone and 4, 4′-bis(4-fluorophthalimido)diphenyl ether (BFPI). The glass transition temperatures and 5% weight loss temperatures in nitrogen of the resulting PESI-C increased from 258°C to 278°C and from 468°C to 495°C with increasing the content of imide moiety in the polymer chain, respectively. These PESI-C films were transparent and essentially colorless and exhibited good mechanical properties with tensile strengths of 91–124 MPa, elongations at break of 6.9–12.8%, and tensile moduli of 2.2–2.8 GPa, respectively. It is noted that the tensile strengths, elongations at break, and tensile moduli of PESI-C also increased with increasing the content of BFPI in the copolymerization, indicating that the properties could be adjusted by controlling the ratio of BFPI and 4, 4′-difluorodiphenyl sulfone.